Indications for Total Hip Arthroplasty in Young Adults – Idiopathic Osteoarthritis Seems To Be Overestimated - Ipach, I.; Mittag, F.; Syha, R.; Kunze, B.; Wolf, P.; Kluba, T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: New aspects like acetabular overcoverage, acetabular retroversion and proximal femoral head-neck dysplasia have been detected as a main cause of osteoarthritis. The study addresses the detection of reasons for osteoarthritis requiring THA in young adults. We wanted to prove the hypothesis that idiopathic reasons play an overestimated role in osteoarthritis in young patients. Materials and Methods: 228 total hip arthroplasties in patients aged ≤ 60 years were performed at our institution. After the detection of the primary reasons for osteoarthritis of the hip, the radiographic pictures of all other patients were analyzed for radiographic signs of hip dysplasia or femoroacetabular impingement. For interobserver quality testing, this was done by two different observers. Results: 132 patients were initially classified as having idiopathic osteoarthritis of the hip. There was no pathological radiographic finding in only 5 patients. 80 patients presented a reduced head-neck offset as a sign of CAM impingement with a mean head ratio of 1.52 ± 0.35 and an alpha angle of 62.8 ± 9.28°. 21 patients presented a figure-8 sign as an indicator for acetabular retroversion. 68 patients presented at least one radiographic finding for “dysplasia” and 60 patients at least one radiographic finding for excessive “overcoverage”. The Bland-Altman Plot for testing interobserver reliability demonstrated good interobserver agreement. Conclusion: Idiopathic OA in young adults is rare if you look hard enough for the underlying pathology. If treated, patients might benefit and THA could be postponed for several years.
Keywords: femur; head/neck; radiography